Insomnia as a rare neuropsychiatric presentation of Wilson disease - Pang, Nicholas Tze Ping; Mat Rosly; Mohamed S (Malaysian Journal of Psychiatry Ejournal, 2015)
Objective: Wilson’s disease (WD) is a rare disorder of copper metabolism with hepatic, neurological and psychiatric manifestations. This case describes insomnia as a rare primary psychiatric presentation of WD. Methods: An 18-year-old gentleman presented with three months of poor sleep. There was no depressive, manic, psychotic, anxiety or cognitive symptoms. He was diagnosed with WD three months ago. Physical examination was normal however Kayser-Fleischer rings were noted. MRI brain demonstrated symmetrical signal abnormalities noted in the head of the caudate nucleus, putamen and globus pallidus. His insomnia worsened on increased dose of chelating agent so the agent was reduced. Longitudinally he developed depressive symptoms so has been commenced on mirtazapine. Discussion: Psychiatric complications of WD are found in initial presentation in 30-67% cases. Underlying scientific mechanisms proposed include brain copper toxicity, presynaptic SERT availability, and alternative metabolic influences. Treatment focuses on chelating agents and psychotropic augmentation.